PENERAPAN NILAI-NILAI TOLERANSI BERAGAMA DALAM PERSEPEKTIF SOSIOLOGI PEMBANGUNAN PADA LEMBAGA DAKWAH KAMPUS: (Studi Di Lembaga Dakwah Kampus Universitas Palangka Raya) - Ferry Setiawan; Ahmad Saefulloh (Journal SOSIOLOGI, 2022)
This paper examines the application of the values of religious tolerance in the perspective of Development Sociology. The purpose of this paper is to see the application of religious tolerance values in the perspective of Development Sociology at the campus da'wah institution. This paper uses descriptive qualitative research methods and uses analysis with an inductive approach, namely the research process and understanding based on methods that investigate a social phenomenon. Techniques in collecting data are observation, interviews and documentation. Based on the data analysis carried out, it was concluded that in the process of applying the values of religious tolerance the Campus Da'wah Institute did not run fully. This 2 depends on the understanding of each member of the LDK, and each member who has a different background and has a different environment so that not all values obtained from the Campus Da'wah Institute can be fully applied. This makes a social construction in it considering the three stages, namely externalization, objectification and internalization take place in it. Meanwhile, in the perspective of development sociology, it can be seen that the application of tolerance values seen from indicators of productivity, efficiency and community participation has been implemented. and each member who has a different background and has a different environment so that not all the values obtained from the Campus Da'wah Institute can be fully implemented. This makes a social construction in it considering the three stages, namely externalization, objectification and internalization take place in it. Meanwhile, in the perspective of development sociology, it can be seen that the application of tolerance values seen from indicators of productivity, efficiency and community participation has been implemented. and each member who has a different.background and has a different environment so that not all the values obtained from the Campus Da'wah Institute can be fully implemented. This makes a social construction in it considering the three stages, namely externalization, objectification and internalization take place in it. Meanwhile, in the perspective of development sociology, it can be seen that the application of tolerance values seen from indicators of productivity, efficiency and community participation has been implemented.